Investigating the determinants of productivity dynamics in Indian commercial banks: a DEA based Malmquist Index approach - Rashika Jain; Mohit Kumar Ojha; Vedmani Mishra (Cogent Business & Management)
This study investigates the dynamics of Total Factor Productivity in Indian banks and drivers of changes in productivity using the panel dataset of 15 private banks and 20 public banks from 2009 to 2019. For this purpose, the study resorted to Data Envelopment Analysis based Malmquist Productivity Index. The findings indicate that Total Factor Productivity growth was mainly recorded in 2011 and 2019 and was influenced by technological progress and efficiency improvements. Rest of the years showed a decline in productivity mainly due to managerial inefficiency. Public-sector banks were more adaptable to technical changes, as 18 out of 20 banks experienced productivity growth. The Central Bank of India was a champion for technical progress. Private sector banks were, however, the hardest hit:12 out of 15 private banks experienced a decline in total factor productivity which occurred mainly due to diseconomies of scale and managerial inefficiencies. The study shows that only three private-sector banks viz. Development Credit Bank, Dhanlaxmi Bank, and IndusInd Bank showed persistent increases in Total Factor Productivity. The empirical findings reflect the productivity gains mainly driven by technical progress in Indian banks. The findings strongly emphasize the need for technological changes to enhance productivity but also reveal the pressing needs of Indian banks, particularly private sector banks, to tackle managerial inefficiency and scale inefficiency. These findings hold deep implications for policymakers looking to shore up the functional and competitive capabilities of the Indian banking sector in the long term.